The lower extremity dexterity test quantifies sensorimotor control for cross-country skiing - Krenn, O.; Werner, I.; Lawrence, E.; Valero-Cuevas, F. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The purpose of this study is to evaluate sensorimotor control of force production in the leg for gliding skills in cross-country skiers in both a one-leg balance task and the recently validated lower extremity dexterity LED test.